Idk tbh so I’m sorry guys lmso
Answer:
sin θ = ![\frac{\sqrt{6} }{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B6%7D%20%7D%7B3%7D)
Step-by-step explanation:
Given that,
cos θ = ![\frac{\sqrt{3} }{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B3%7D%20%7D%7B3%7D)
From the trigonometric functions,
cos θ = ![\frac{adjacent}{hypotenus}](https://tex.z-dn.net/?f=%5Cfrac%7Badjacent%7D%7Bhypotenus%7D)
⇒ adjacent =
, and the hypotenuse = 3
Let the opposite side be represented by x, applying the Pythagoras theorem we have;
=
+ ![/opp/^{2}](https://tex.z-dn.net/?f=%2Fopp%2F%5E%7B2%7D)
=
+ ![x^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D)
9 = 3 + ![x^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D)
= 9 - 3
= 6
x = ![\sqrt{6}](https://tex.z-dn.net/?f=%5Csqrt%7B6%7D)
Thus, opposite side = ![\sqrt{6}](https://tex.z-dn.net/?f=%5Csqrt%7B6%7D)
So that,
sin θ = ![\frac{opposite}{hypotenuse}](https://tex.z-dn.net/?f=%5Cfrac%7Bopposite%7D%7Bhypotenuse%7D)
= ![\frac{\sqrt{6} }{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B6%7D%20%7D%7B3%7D)
Therefore,
sin θ = ![\frac{\sqrt{6} }{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B6%7D%20%7D%7B3%7D)
Answer:
x=0, y=1
Step-by-step explanation:
Evaluate basically just means to solve.
Replace the given vaule of m into the equation to get -8/2.
Then solve.
-8 divided by 2 is -4
X=b/a and next time include the what the following are